PROBLEMS OF SELECTION OF FEMALE ATHLETES FOR THE FORMATION OF FORMATION TEAMS IN ACROBATIC ROCK 'N' ROLL - Galyna Artemyeva; https://orcid.or 0002-6965-4972 (Kharkiv State Academy of Physical Culture, 2021)
Purpose: the substantiation of the most significant components of the comprehensive assessment of the results of the competitive program, which will determine the effectiveness of the composition of athletes for the teams of formation in the acrobatic rock 'n' roll. Material and methods: research was conducted on the basis of clubs from the acrobatic rock and roll of the All-Ukrainian public organization "Federation of Acrobatic rock and roll of Ukraine" (FARRU). The study participated athletes of Female Command formation aged 13 to 28 years in an amount of 84 people. Qualification: 19 athletes (22,6 %) have the first discharge, 46 athletes (54.8%) have a discharge of KMS, 19 athletes (22,6 %) of the MS of Ukraine. To achieve the goal we used a complex of modern research methods: theoretical analysis and generalization of literary and Internet sources, analysis of documentary materials, pedagogical observation, anthropometry, methods of mathematical statistics. Results: the conducted study made it possible to determine the harmonism of the structure of teams by their components and the influence of components for a comprehensive assessment for the implementation of competitive exercises. Conclusions: as a result of the use of modern research methods managed to establish components of the contingent structure and determine the elements of the evaluation system for forming commands in the category of Female formations in the Acrobatic rock 'n' roll.